PENGARUH RASIO LIKUIDITAS DAN RASIO SOLVABILITAS TERHADAP RASIO PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA - Gultom, Fratis F. (Jurnal Manajemen dan Bisnis, 2010)
Calculation of financial ratios is one of the financial statement analysis tools to compare the data with other data, to determine the interrelationships between assets, liabilities and capital which can then be determined level of liquidity, solvency and profitabilitas.Berdasarkan preliminary research note that the ratio - financial ratios ( liquidity ratio and solvency ratio) of manufacturing companies that have gone public on the Jakarta Stock Exchange has a different relationship when associated with profitabiitas. Based on the description, research the problem can be formulated as follows: "Is the liquidity ratio and solvency ratio has a significant influence on the profitability ratios of manufacturing companies in Jakarta Stock Exchange?" Population is the total number of objects to be observed or researched. This study population is a manufacturing company in Jakarta Stock Exchange as many as 153 companies. Sample is part of the population. Study sample are liquidity ratios, solvency ratios and profitability ratios 34 manufacturing firms in 2001-2003. Secondary data collection techniques through technical documentation. data analysis technique used is multiple linear regression method to clarify the effect of liquidity ratios and solvency ratios of profitability ratios. Based on the results of the discussion, it can be concluded that the results obtained that simultaneous analysis of liquidity ratios there is no significant effect on the profitability of the company. It can be seen from the f-count 2)ï¡t As for suggestions that can be given the author is a company should manage current ratio (current assets and current liabilities) well to a good level of liquidity memeproleh company can enhance its liquidity by increasing current assets but remains current debt, or should reduce current debts but assets remain . In order to achieve the planned levels of profitability then the management must be able to properly manage and loans for a number of assets owned memebiayai so as to increase profits of manufacturing companies in Jakarta Stock Exchange